WORK CULTURE, COMPENSATION, THE INFLUENCE ON EMPLOYEE PERFORMANCE, BTN BANK, SURABAYA BRANCH - Marpaung, Daulat (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2021)
Competition in the banking industry is very high at this time, it is necessary to have highemployee performance to be able to compete. This study aims to determine the impact ofSIIPS work culture and compensation on the performance of employees of Bank BTNSurabaya Branch. This research uses a quantitative approach with survey research methods.The research instrument consisted of work culture, compensation and performancequestionnaires. The results showed that: 1). SIIPS work culture has a positive direct effecton performance, 2). Compensation has a positive direct effect on performance 3). SIIPSwork culture and compensation simultaneously have a positive direct effect on performance.Keywords: banking industry, SIIPS work culture, compensation, and performance